Harmfulness of cryptid and cabbage pod mosquito of the Steppe zone of Ukraine - Bashchenko, M.; Shyta, O.; Bondar, T.; Fedorenko, А.; Chelombitko , A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. To specify the species composition of phytophages and to investigate their harmfulness in winter rapeseed crops.Methods. The research was conducted in the Steppe zone in 2022 (Odesa region, Odesa district, Khlybodarske settlement, «Odesa State Agricultural Research Station of the Institute of Water Problems and Land Reclamation of the National Academy of Sciences»). Clarification of the species composition and the dynamics of the number of phytophages was carried out according to generally accepted methods.Results. During the surveys, insects belonging to 6 orders (Coleoptera, Heteroptera, Hemiptera, Diptera, Hymenoptera and Lepidoptera) were found, of which 47,3% were direct pests of winter rape, 10.8% were pests of grain crops (there were fields nearby, and research plots of grain and ear crops), and 41.9% are entomophages. At the time of research, there were an average of 46 rapeseed plants per 1 m2, with 36.7 ± 2.19 pods per plant. During visual inspections before harvesting, characteristic damage by the cabbage stem borer (Ceutorhynchus quadridens Panz.) was noted on the rape stalks — 31.0% of plants/ m2, and the plants were broken near the root neck. During the growth of the stem, the larval stages of this pest were found, which penetrated into the middle, biting the petiole of the leaf, then moved to the root neck, where they fed on the tissues of the plant for a long time, causing its fragility. It was found that damage to pods per 1 m2 was 21.9%. Of them, the seed gnat (Ceutorhynchus assimilis Payak.) — 18.0%, the cabbage pod mosquito (Dasyneura brassicae Winn.) — 3.9%. Total crop losses from the above-mentioned pests on winter rapeseed crops amounted to — 52.9%.Conclusions. It was established that the share of pests in the entomocomplex of rape agrocenosis was — 47.3%. Damage to winter rapeseed crops by cabbage seed borer was — 18.0%, cabbage pod mosquito — 3.9%, and cabbage stem borer — 31.0%, which in total resulted in 52.9% yield loss.